New combinations and synonymies for Neotropical species of Diaphorinae (Diptera: Dolichopodidae). - Soares Capellari, Renato; de Souza Amorim, Dalton (Contributions to Entomology = Beiträge zur Entomologie, 2014)
Based on examination of the Dolichopodidae (Diptera) material in the Senckenberg Naturhistorische Sammlung Dresden, eight Neotropical species of Diaphorus Meigen are herein transferred to the genus Chrysotus Meigen: C. amicus (Parent), comb. n.; C. ciliatus (Becker), comb. n. (= C. superbiens (Parent), comb. n. et syn. n.); C. hamatus (Parent), comb. n.; C. vicinus (Becker), comb. n., nec Parent; C. luteipalpus (Parent), comb. n.; C. mediotinctus (Becker), comb. n.; C. propinquus (Becker), comb. n. Additionally, C. kallweiti Capellari & Amorim, nom. n. is proposed as a replacement name for C. vicinus Parent, nec C. vicinus (Becker), comb. n., and C. diligens Parent is found to be a junior-synonym of C. viridis Becker. Lectotype and paralectotypes are designated for species with syntypes in their type-series. The mediotinctus-group is proposed within Chrysotus for a small clade including five South American species, and an identification key to the species of the group is provided.KeywordsDiaphorus, Chrysotus, Dubius, Staatliches Museum für Tierkunde DresdenNomenclatural Actsamicus (Parent, 1931) (Chrysotus), comb. n. hitherto Diaphorus amicus Parent, 1931ciliatus (Becker, 1922) (Chrysotus), comb. n. hitherto Diaphorus ciliatus Becker, 1922diligens Parent, 1931 (Chrysotus), LT; syn. n. of Chrysotus viridis Becker, 1922hamatus (Parent, 1931) (Chrysotus), comb. n. hitherto Diaphorus hamatus Parent, 1931luteipalpus (Parent, 1929) (Chrysotus), comb. n. hitherto Diaphorus luteipalpus Parent, 1929mediotinctus (Becker, 1922) (Chrysotus), LT; comb. n. hitherto Diaphorus mediotinctus Becker, 1922propinquus (Becker, 1922) (Chrysotus), LT; comb. n. hitherto Diaphorus propinquus Becker, 1922vicinus (Becker, 1922) (Chrysotus), LT; comb. n. hitherto Diaphorus propinquus Becker, 1922superbiens Parent, 1931 (Diaphorus), syn. n. of Chrysotus ciliatus (Becker, 1922)